The Effect of Job Stress due to Environmental Changes and Compensation on Teachers’ Performance in Palembang City - Nurika, Ellaine; Sukarim, Rivaldi (Journal of Advances in Accounting, Economics, and Management, 2023)
In a corporate context, the success of an employees in performing their jobs can be measured by the low levels of job stress they experience, and it is known that there is a direct relationship between stress and performance, because when an employees have a high level of stress, the employee won’t be able to work efficiently and optimally. This can happen not only to office employees, even teachers can experience job stress. Job stress experienced by a teacher certainly has the possibility of interfering with his productivity and of course can affect the students he teaches. Compensation is one of the things that is considered to improve performance. This research was conducted to find out whether the compensation given was able to have a positive impact on the performance of these teachers and guarantee their performance. Data used in this research we’re collected from 106 respondents and after a several tests, the result is both of the job stress that the teachers felt and the compensation that given by the company can make a positive effect on job performance, that can be interpreted as if job stress reduced, the teacher’s performance will increase. And conversely if the compensation increases, the performance will also increase.